Stability of domain 4 of the anthrax toxin protective antigen and the effect of the VWA domain of CMG2 on stability. (February 2017) - Mamillapalli, Sireesha; Miyagi, Masaru; Bann, James G.
Abstract: The major immunogenic component of the current anthrax vaccine, anthrax vaccine adsorbed (AVA) is protective antigen (PA). We have shown recently that the thermodynamic stability of PA can be significantly improved by binding to the Von‐Willebrand factor A (VWA) domain of capillary morphogenesis protein 2 (CMG2), and improvements in thermodynamic stability may improve storage and long‐term stability of PA for use as a vaccine. In order to understand the origin of this increase in stability, we have isolated the receptor binding domain of PA, domain 4 (D4), and have studied the effect of the addition of CMG2 on thermodynamic stability. We are able to determine a binding affinity between D4 and CMG2 (∼300 n M ), which is significantly weaker than that between full‐length PA and CMG2 (170–300 p M ). Unlike full‐length PA, we observe very little change in stability of D4 on binding to CMG2, using either fluorescence or 19 F‐NMR experiments. Because in previous experiments we could observe a stabilization of both domain 4 and domain 2, the mechanism of stabilization of PA by CMG2 is likely to involve a mutual stabilization of these two domains.